Postcards from the Field - Jennifer Cruse-Sanders (Sibbaldia, 2017)
Increasingly, botanic gardens and arboreta are highlighted as effective partners to conserve plant species diversity and restore natural communities at a time when the need for these activities has become more urgent. Capacity for restoration and conservation at botanic gardens comes directly from staff expertise for horticulture and research. Botanic gardens make good partners for connecting botanical science with conservation practice. They are in a position to communicate information about rare plant species to owners and managers of public and private lands, and they can be instrumental in creating networks for effective conservation action. Several examples from south-eastern United States of America illustrate how this has been put into practice. These examples provide evidence that efforts to expand collaboration between federal agencies, states and non-governmental organisations can lead to effective alliances to conserve plant biodiversity, especially when plants receive a disproportionately low share of resources for conservation.